2015
DOI: 10.1111/jvim.12546
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Vitamin D Metabolites and C‐Reactive Protein in Stage‐Stop Racing Endurance Sled Dogs

Abstract: BackgroundDogs are a unique model for examining the effects of exercise on vitamin D status because of their lack of vitamin D synthesis by UV exposure. In addition, the inflammatory response may be associated with hypovitaminosis D.ObjectivesTo investigate the effects of several days of endurance exercise on plasma vitamin D (25‐(OH)D3, 24,25‐(OH)D3 and 1,25(OH)D3) and serum C‐reactive protein (CRP) concentrations in stage‐stop racing sled dogs.Animals12 racing sled dogs and 8 control dogs.MethodsBlood was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 59 publications
3
28
0
Order By: Relevance
“…This may be true for all dogs, but studies confirming this finding in other breeds are needed. Additionally, 24,25(OH) 2 D concentrations in dogs appear to be much higher than those reported in humans and other species . This observation is most likely a consequence of higher dietary vitamin D intake in dogs through the consumption of commercial dog foods fortified with vitamin D. The relationship between dietary vitamin D intake and plasma 25(OH)D may be harder to quantify in dogs that are receiving amounts of vitamin D over intake requirements.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This may be true for all dogs, but studies confirming this finding in other breeds are needed. Additionally, 24,25(OH) 2 D concentrations in dogs appear to be much higher than those reported in humans and other species . This observation is most likely a consequence of higher dietary vitamin D intake in dogs through the consumption of commercial dog foods fortified with vitamin D. The relationship between dietary vitamin D intake and plasma 25(OH)D may be harder to quantify in dogs that are receiving amounts of vitamin D over intake requirements.…”
Section: Discussionmentioning
confidence: 89%
“…Factors shown to influence blood 25(OH)D concentrations in humans include the following: sex, sex hormone concentrations, age, race, body condition score (BCS), muscle condition score (MCS), dietary vitamin D intake, blood ionized calcium concentrations (ICa), and blood parathyroid hormone concentrations (PTH) . Additionally, blood concentrations of another vitamin D metabolite, 24,25(OH) 2 D, have been reported to be much higher in dogs than in other species . Thus, activity of the 25‐hydroxyvitamin D‐24‐hydroxylase enzyme (CYP24A1), which is responsible for converting 25(OH)D to 24,25(OH) 2 D, may be an important factor determining blood 25(OH)D concentrations.…”
mentioning
confidence: 99%
“…A recent study has found that plasma concentrations of 24,25(OH)D 3 , an excretory metabolite of 25(OH)D, were higher in dogs than in humans, pigs and rodents indicating that the metabolism of 25(OH)D may be different between dogs and other species (Spoo et al . ). The nuclear VDR is the ligand‐dependent transcription factor that mediates the action of its natural ligand 1,25(OH) 2 D (Vanherwegen et al .…”
Section: Vitamin D – An Overviewmentioning
confidence: 97%
“…, Spoo et al . ). There is a need to further clarify whether vitamin D deficiency is a cause or consequence of inflammation in companion animals.…”
Section: Vitamin D – An Overviewmentioning
confidence: 97%
See 1 more Smart Citation